اتجاهات اساتذة الجامعة نحوتوظيف الفتاوى الدينية عبر الفضائيات في الأزمة السعودية القطرية - غريسي, نسيمة (University of Eloued جامعة الوادي, 2018)
"ملخص الدراسة باللغة العربية هدفت الدراسة إلى التعرف على اتجاهات أساتذة الجامعة نحو توظيف الفتاوى الدينية في الأزمة السعودية القطرية , حيث اعتمدنا على المنهجين الوصفي والمسحي , من خلال المسح بالعيّنة لأساتذة جامعة الشهيد حمّه لخضر بالوادي , وبلغ حجم العينة (116) أستاذ , معتمدين على أداة الاستبيان لجمع المعلومات . وقد توصلت الدراسة إلى أهم النتائج التالية : - أن دوافع تعرض أساتذة الجامعة لأخبار الأزمة السعودية القطرية دوافع نفعية . - اتجاهات أساتذة جامعة نحو توظيف الفتاوى الدينية في الأزمة السعودية القطرية اتجاه محايد. -اتجاهات أساتذة جامعة نحو تأثر الفتاوى الدينية بالنظم السياسية ومسايرتها للمصالح السياسية للدول اتجاه سلبي. - اتجاهات أساتذة جامعة نحو توظيف الفتاوى الدينية في الأزمة السعودية القطرية من أجل تدعيم الأزمة والمواصلة فيها تشريع الحصار اتجاه سلبي. ""This study aimed to identify the attitudes of the university professors to words the use of religious opinions )FATWAS( in the sauid-qatari crisis . In this research , we relied on a descriptive survey approache. Throughout a sample survey of professors of "" Martyr HAMA LAKHDER university-ELOUED "" . The sample contained 116 professors . we relied on the questionnaire tool for collecting in formations . The study contuded to the following important results: - The motivation of university professors to news about the sauid-qatari crisis was of utilitarian considerarions . - Attitudes of university professors the use of religious opinions in the sauid-qatari crisis was in a neutral trend . - Attitudes of university professors to words the use of religious opinions has an effect an political systems and its equality to the interest of states in a negative way . - Attitudes of university professors to words the use of religious opinions in the sauid-qatari crisis in order to contain the crisis and continue in it in a negative way .
مذكرة ماستر تخصص دعوة واعلام
Keywords: ". الاتجاهات • أساتذة الجامعة • الفتاوى الدينية • الأزمة السعودية القطرية "; "Tendes - University professors. –Religions opinions- Saudi-Qutari crisis"